Research Trends on Entrepreneurship in the Tourism Sector - Gonzalez-Candia, J (Inderscience Publishers, 2024)
Entrepreneurship in tourism drives innovation, job creation, and contributes to the economic growth of communities. However, despite its great importance, the current trends in the field are unknown. Therefore, the objective is to examine research trends surrounding entrepreneurship in the tourism sector. The study proposes a bibliometric analysis to explore the scientific and academic evolution of tourism, following PRISMA-2020 standards. The bibliometric analysis reveals a significant growth in publications on entrepreneurship in tourism, identifying prominent researchers and emerging topics such as FSQCA, entrepreneurial intention, and sustainability, while social entrepreneurship emerges as the predominant theme in the field. © © 2024 Inderscience Enterprises Ltd.